Preschool Teachers' Views and Practices on Sexual Development and Education: A Case Study - Yalkılıç, Beyza; YAĞAN, SEVCAN (Anı Publishing, 2023)
This study aimed to examine the views and practices of preschool teachers on sexual development and education. The research was carried out with a case study design, one of the qualitative research designs, and the data were collected in the spring term of the 2019-2020 academic year. The working group consisted of 10 preschool teachers with5 years or more of professional experience working with 36-72-month-old children. A demographic information form, a semi-structured interview form, and a document review form were used to collect data. In the analysis of the research data, the descriptive analysis method was used for the interview data, and the content analysis method was employed in the document review form. According to the study results, preschool teachers did not have sufficient knowledge about the content of sexual education, children did not direct questions to their teachers about sexual development, and teachers did not encourage children to ask questions despite this situation. The study determined that only 28 of the 100 activity plans implemented by preschool teachers in the classroom included comprehensive sexual education topics.
Keywords: Preschool Teachers; Preschool Education; Sexual Development; Sexual Education; Child Development